An Approximation Algorithm for Energy-Efficient Scheduling on A Chip Multiprocessor - Yang, Chuan-Yue; Chen, Jian-Jia; Kuo, Tei-Wei (Design, Automation and Test in Europe, 2005)
In the recent decade, voltage scaling has become an attractive feature for many system component designs. In this paper, we consider energy-efficient real-time task scheduling over a chip multiprocessor architecture. The objective is to schedule a set of frame-based tasks with the minimum energy consumption, where all tasks are ready at time 0 and share a common deadline. We show that such a minimization problem is NP-hard and then propose a 2 .371-approximation algorithm. The strength of the proposed algorithm was demonstrated by a series of simulations, for which near optimal results were obtained.